Resíduos sólidos orgânicos no município de Arraias - Tocantins - revisão de literatura e propostas educativas - Santos, Gabrielle Moreira dos (Universidade Federal do Tocantins, 2023)
This monographic work presents a literature review on urban organic solid waste, referencing the understanding of the processes that involve from their generation, disposal and processing in the Municipality of Arraias, Tocantins. Through research in the scientific literature and specific legislation, the work seeks to delimit the understanding concerning the theme by correlating this process to the aforementioned city, pointing out the problems observed both in human health and in the environment due to the arbitrary handling of organic solid waste: among mentioned are leachate, the emission of methane gas, the diseases that manifest themselves in situations linked to the proliferation of vectors such as rats, flies and others. It also addresses the exposition of laws that support and regulate the National Solid Waste Policy, as well as the inference to the Quintuple R of sustainability and BNCC in the educational system, correlating them with the proposals listed in the 2030 Agenda and the SDGs - Sustainable Development Goals. In this way, it is intended to approach the investigation in the urban environment of the city of Arraias, working on the destination of organic solid waste originated in scale in the various segments of the Arraiana society. The contextualization also lists some suggestions for problems related to the disorderly accumulation of solid waste production, such as: the elaboration and implementation of a Municipal Solid Waste Management Plan, composting in households, and the implementation of a composting plant in the municipality or in an inter-municipal consortium and more: the work makes a contribution to the county, by preparing an illustrated educational booklet, producing an awareness and learning instrument about organic solid waste with the municipal school community.